Mother Teresa : An Authorized Biography - Kathryn Spink (HarperOne, 2011)
"Newly revised and updated, here is the complete story of Mother Teresa of Calcutta, founder of the Missionaries of Charity and winner of the Nobel Peace Prize, a woman regarded by millions as a contemporary saint for her dedication to serving the poorest of the poor. From her childhood in the Balkans as a member of a remarkably openhearted and religious family to her work in India, from attending the victims of war-torn Beirut to pleading with George Bush and Saddam Hussein to choose peace over war, Mother Teresa was driven by an absolute faith. During her lifetime, Mother Teresa resisted having her full biography written. Then in 1991, realizing that accounts of her life and work could inspire others, she gave Kathryn Spink, who had long been intimately involved with the work of Mother Teresa and her order, permission to proceed with a complete biography on the understanding that it would not be finished until after her death (September 5, 1997). This revised and updated edition will include: - The beatification and continuing process of canonization for Mother Teresa - What happened to the Missionaries of Charity after her death - An intimate look into Mother Teresa's "dark night of the soul" which has garnered much media attention in recent years, including a published book of her journals (Come Be My Light) Mother Teresa consistently claimed that she was simply responding to Christ's boundless love for her and for all of humanity, bringing to the world a great and living lesson in joyful and selfless love. This book is a special look into her extraordinary faith, work, and life"